Research Submission: Noise as a Trigger for Headaches: Relationship Between Exposure and Sensitivity - Martin, Paul R; Reece, John; syth, Michael (Headache, 2006)
Objective.-This study investigated how triggers acquire the capacity to precipitate headaches. Background.-Traditional clinical advice is that the best way to prevent headache-migraine is to avoid the triggers. Avoidance of anxiety-eliciting stimuli, however, results in sensitization to the stimuli, so is there a danger that avoidance of migraine-headache triggers results in decreased tolerance for the triggers? Design.-One hundred and fifty subjects, 60 of whom suffered from regular headaches, were randomly assigned to 5 experimental conditions, defined by length of exposure to the headache trigger of noise. Methods.-Subjects attended a laboratory session divided into 3 phases: preintervention test, intervention (1 of 5 levels of exposure to the trigger), and postintervention test. Response to the intervention was measured in terms of noise tolerance, sensitivity to noise, and nociceptive response to noise. Results.-A curvilinear relationship was found between length of exposure to the trigger and pain response for individuals who do not suffer from regular headaches, that is, short exposure was associated with sensitization and prolonged exposure with desensitization. The relationship for headache patients was less clear. Conclusions.-The findings are consistent with the proposition that 1 etiological pathway to suffering from frequent headaches is via trying to avoid, or escape from, potential trigger factors. These results suggest that the traditional clinical advice to headache patients, that the best way to prevent migraine-headache is to avoid the triggers, runs the risk of establishing an insidious sensitization process thereby increasing headache frequency.